(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This article is component three of the Project: Proposal of a preventive strategy to reduce the incidence of type 2 diabetes in the province of Santa Elena 2019 – 2021, was developed under the context of a provision of the National Assembly of Ecuador as an action to give attention to all people living with diabetes and especially as a measure of control of the incidence.